2004
DOI: 10.1021/om0493412
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Complexes with 3-Alkyl-Substituted-1,10-Phenanthrolines:  Effect of the Remote Alkyl Substituent on the CO/Olefin Copolymerization Reactions

Abstract: The coordination chemistry of a series of 3-alkyl-substituted-1,10-phenanthrolines (3-Rphen) to palladium as well as the catalytic behavior of the corresponding bischelated derivatives, [Pd(3-R-phen) 2 ][PF 6 ] 2 , in the CO/vinyl arenes copolymerization reaction has been investigated in detail. The alkyl substituents differ in length and steric hindrance. The crystal structure characterization reveals that the two molecules of 3-R-phen are bound to palladium in a syn arrangement with the alkyl groups on the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
55
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 55 publications
8
55
0
Order By: Relevance
“…In a previous paper in which some of the same ligands employed here had been tested, it had been noted that a higher productivity was obtained with unsubstituted styrene, 17 contrary to what was generally reported in the literature. 39,[40][41][42][43] The new, more extensive, series of data supports this observation, but also shows that the higher activity is also associated with a faster deactivation, since not only k 1 , but also k 3 values are consistently higher in the case of styrene. To the best of our knowledge, an active role of the olefin in the deactivation process has not been proposed before.…”
Section: Fitting Of the Data Of The Styrene Experiments Run Under 5 Bsupporting
confidence: 59%
See 2 more Smart Citations
“…In a previous paper in which some of the same ligands employed here had been tested, it had been noted that a higher productivity was obtained with unsubstituted styrene, 17 contrary to what was generally reported in the literature. 39,[40][41][42][43] The new, more extensive, series of data supports this observation, but also shows that the higher activity is also associated with a faster deactivation, since not only k 1 , but also k 3 values are consistently higher in the case of styrene. To the best of our knowledge, an active role of the olefin in the deactivation process has not been proposed before.…”
Section: Fitting Of the Data Of The Styrene Experiments Run Under 5 Bsupporting
confidence: 59%
“…This trend is in agreement with the productivity data obtained in the batch copolymerization reactions, 17 but is the opposite of that found in the case of the phenanthroline-containing catalysts. 21,43 The kinetic analysis shows that the higher activity of the present catalysts in the CO/styrene copolymerization is also associated with a faster deactivation, since not only k 1 , but also k 3 values are consistently higher than in the case of 4-Me-styrene (Tables 2 and 3). The values of the kinetic constants highlight that in the series of the catalysts with the symmetric Ar-BIANs, those with electron-donating substituents show the lowest propagation and decomposition rate, while the ligands symmetrically substituted with CF 3 or F yield the most active catalysts, but also show the highest deactivation rate, in particular in the CO/4-Mestyrene copolymerization.…”
Section: General Trends In the Activity Vs Time Plotsmentioning
confidence: 79%
See 1 more Smart Citation
“…The latter trend is in agreement with mosto ft he catalytic systems described in the literature, for whicht he introductiono fa na lkyl group in para position on the vinyl arene comonomer resulted in an enhanced reactivity. [16,51] The opposite trend, analogous to that observedh erefor 1b,was,however,reported forpalladium catalysts containing bis(aryl-imino)acenaphthenes,f or which productivities in the CO/MSc opolymerization were similaro rl ower compared to those obtained in the CO/S counterpart. [22,49] The literature catalytic systemsw ith iminopyridines showedr emarkably lower productivities than those reported here, that is, from 0.097 to 0.541 kg CP g Pd…”
Section: Co/vinylarene Copolymerization Reactionsmentioning
confidence: 58%
“…For all the three vinyl arenes, moving from the aldimine to the ketimine catalyst, as teep improvement of the Mw values was achieved,y ielding polyketones with Mw data ranging from 250 000 to almost 500 000 gmol À1 ,w hich are among the highest reported so far. [16,51] Thei ncreasei nt he molecular weight indicated that the increase in the productivity obtained with 2b was due to an increase in the length of the polymer chains rather than in their number,a sa lso revealed by the differences in the turnover numbers (TON, Ta ble 1). This suggests that, in the case of the ketimine catalyst, the increase in the ratio between the propagation and the terminationr ate might be due to both an increaseinthe propagation rate and adecreaseinthe termination rate.…”
mentioning
confidence: 99%